THE ROLE OF CIREUNDEU TRADITIONAL VILLAGE IN TOURISM MANAGEMENT - Satrio N. M.; Ahmad Hudaiby Galih Kusumah (UNIVERSITAS PAKUAN, 2022)
Traditional village is an area that is managed by a community with certain customary rules and has a strong relationship with the environment. These customary rules have the aim of maintaining the sacredness of the region and the culture that has been passed down from generation to generation. Cireundeu Traditional Village is one of many traditional villages in West Java, located in Leuwigajah Village, South Cimahi District, Cimahi City. The research, entitled